Comparison of Process Stability in Methane Generation from Palm Oil Mill Effluent using Dairy Manure as Inoculum - Krishnan, Santhana; Singh, Lakhveer; Puranjan, Mishra; Mohd, Nasrullah; Mimi Sakinah, A. M.; Thakur, Sveta; Siddique, Md. Nurul Islam; Zularisam, A. W. (Elsevier, 2017)
The potential of methane production in a continuously stirred tank reactor (CSTR) was investigated using dairy manure as inoculum at pH 6.8 and 37 °C temperature in this study. Two identical anaerobic bioreactors namely CSTR1 and CSTR2 filled with palm oil mill effluent (POME) as a carbon source were used. CSTR1 was not added with the inoculum, while CSTR2 was added with dairy manure as inoculum. Both the reactors were allowed to run for 5 days (d) in batch condition at hydraulic retention time (HRT) 10 d. The CSTR2produced 0.85 L/d gas yield and 59% methane content compared to 0.39 L/d gas yield and 20% produced in CSTR1, respectively. A better chemical oxygen demand (COD) reduction percentage of 48% was found in CSTR2 compared to CSTR1 with 33%. The investigation showed that dairy manure as inoculum has a marked influence on the start-up period and the biogas production rate.